2021
DOI: 10.2147/dmso.s315488
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Competitive Endogenous RNA Network Mechanism in Type 1 Diabetes Mellitus Using Computational and Bioinformatics Approaches

Abstract: Background: Type 1 diabetes mellitus (T1DM), an autoimmune disease with a genetic tendency, has an increasing prevalence. Long non-coding RNA (lncRNA) and circular RNA (circRNA) are receiving increasing attention in disease pathogenesis. However, their roles in T1DM are poorly understood. The present study aimed at identifying signature lncRNAs and circRNAs and investigating their roles in T1DM using the competing endogenous RNA (ceRNA) network analysis. Methods: The T1DM expression profile was downloaded from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Additionally, 1922 markedly expression circRNAs were found in mouse islet β-cells induced by various cytokines, such as interleukin-1β (IL-1β), interferon-γ(INF-γ), and tumor necrosis factor-α (TNF-α) ( Wang et al, 2021a ). In order to clarify the role of circRNA in T1D, Yi et al ( Yi and Cheng, 2021 ) established the circRNA-lncRNA-miRNA-mRNA ceRNA regulatory network for T1D using computational and bioinformatic approaches. However, studies on therapeutic circRNAs in T1D are limited, it needs to be proven by a large amount of data in the future.…”
Section: Circrnas and Different Types Of Diabetesmentioning
confidence: 99%
“…Additionally, 1922 markedly expression circRNAs were found in mouse islet β-cells induced by various cytokines, such as interleukin-1β (IL-1β), interferon-γ(INF-γ), and tumor necrosis factor-α (TNF-α) ( Wang et al, 2021a ). In order to clarify the role of circRNA in T1D, Yi et al ( Yi and Cheng, 2021 ) established the circRNA-lncRNA-miRNA-mRNA ceRNA regulatory network for T1D using computational and bioinformatic approaches. However, studies on therapeutic circRNAs in T1D are limited, it needs to be proven by a large amount of data in the future.…”
Section: Circrnas and Different Types Of Diabetesmentioning
confidence: 99%
“…It has been reported that miRNAs, as conserved non-coding single-stranded RNA molecules, are involved in a variety of physiological and pathological processes [ 24 ]. As a sponge of miRNAs, lncRNA forms the corresponding lncRNA/miRNA axis to regulate transcription and tumor cell proliferation [ 25 , 26 ]. This study predicted that LINC00943 and miR-196b-5p have binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Key ceRNA pairs in metabolic pathways may participate in right ventricular dysfunction (52). circRNA/lncRNA/miRNA/mRNA inhibits macrophage inflammation in type 1 diabetes mellitus (T1DM) (53). AC063977.6/miR-338-3p/PFKFB2 may regulate metabolic event during Intervertebral disc degeneration (IDD) pathogenesis (54).…”
Section: Discussionmentioning
confidence: 99%